Integrated approach for identifying and evaluating the quality of Marsdenia tenacissima in the medicine market - Yu, Ning; Wei, Yu-long; Zhu, Yue; Zhu, Ning; Wang, Yan-li; Zhang, Hai-ping; Sun, Ai-dong (PLOS ONE, 2018)
The accurate identification and quality evaluation of herbal medical plants is highly necessary to ensure their safety and efficacy. In present study, a new strategy combining DNA barcoding techniques with thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC) was proposed to facilitate the identification and quality control of M. tenacissima. In present work, the internal transcribed spacer 2 (ITS2) barcode was successfully used to identify 58 M. tenacissima samples and its adulterants. TLC successfully identified the other three M. tenacissima samples that failed to produce ITS2 regions. An adulterant was found in all the 62 samples. Moreover, the content of active medicinal ingredients is important for herbal plants quality. The content of tenacissoside H (TS-H) of M. tenacissima samples was determined by HPLC to range from 0.39% to 1.09%, which meets the criterion of the Chinese Pharmacopoeia. Thus, DNA barcoding coupled with TLC and HPLC is very promising to identify and evaluate the quality of M. tenacissima in the medicine market.